2013
DOI: 10.5352/jls.2013.23.5.698
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Feeding with High γ-Aminobutyric Acid (GABA) Containing Giant Embryo Black Sticky Rice (Oryza sativa L.) on Alcohol Intake in C57BL/6 Mice

Abstract: It is known that black sticky rice with giant embryo (BSRGB, Milyang 263) and giant embryo rice (GER) contains higher levels of GABA than rice. Therefore, feeding BSRGB, GER, or rice freely to C57BL/6 mice with two-hour alcohol intake for 16 days was investigated. For two-hour alcohol intake, a repeated measure ANOVA (three treatment groups repeated across 16 days; 8 two-day blocks) yielded a significant group by block interaction (df=16, F=3.109, p=0.004). The independent t-test showed that significant suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…They suggested that a limited diffusion of GABA from blood into brain induced physiological changes in monoaminergic neurons. Thus, although the results of this study cannot conclusively determine whether BSRGE GABA component can pass through BBB, daily intake of BSRGE in previous studies altered the degree of alcohol intake [11], alcohol-related indices [12] and anxiety-related behaviors [13] and its results may be related to an increase of GABA concentration and neurotransmission in CNS after BSRGE intake.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…They suggested that a limited diffusion of GABA from blood into brain induced physiological changes in monoaminergic neurons. Thus, although the results of this study cannot conclusively determine whether BSRGE GABA component can pass through BBB, daily intake of BSRGE in previous studies altered the degree of alcohol intake [11], alcohol-related indices [12] and anxiety-related behaviors [13] and its results may be related to an increase of GABA concentration and neurotransmission in CNS after BSRGE intake.…”
Section: Discussionmentioning
confidence: 69%
“…Investigations suggest an association between alcohol intake, alcohol-related indices and effects of BSRGE. Kim et al [11] reported that feeding BSRGE freely to C57BL/6 mice induced a significant decline in 2-h alcohol intake compared with the control group. The changes in 2-h alcohol intake were attributed to higher GABA levels in BSRGE than in the general brown rice.…”
Section: Introductionmentioning
confidence: 99%
“…An animal testing with BSRGE indicated a change of alcohol intake. Kim and colleagues () reported that feeding BSRGE freely to C57BL/6 mice had a significant suppression of 2‐hour alcohol intake, compared with control groups. The authors presumed the change of 2‐hour alcohol intake is caused by GABA, which is found in higher levels in BSRGE than in general brown rice (Kim et al., ).…”
Section: Physicochemical Property Of “Nunkeunheugchal”mentioning
confidence: 99%